PERANCANGAN VIDEO IKLAN MOTION GRAPHIC SEBAGAI STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PRODUK UMKM VYCTORY BAKERY & SNACK - Lindartono, Gabriella Florencia Sonatha; Irdha Yunianto; Aris Sarwo Nugroho (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to design and develop a motion graphic advertisement video as a digital promotion strategy for the MSME Vyctory Bakery & Snack. The research utilizes the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The final product consists of two advertisement videos with a duration of 30–40 seconds each. The evaluation was conducted using a questionnaire based on a five-point Likert scale to assess the feasibility in terms of design, information, as well as editing and animation aspects. The results indicate that the advertisement videos fall within the “good” to “very good” category, demonstrating their effectiveness and efficiency as digital promotional media for MSMEs.